The stars beneath our feet [large type] - Moore, David Barclay (Thorndike Press, 2018)
Lolly Rachpaul, twelve, still reeling from the shooting death of his older brother, begins to find his own way--without gang alliances--when his mother's girlfriend's gift of Legos allows him to build a fantastical city at a Harlem community center.